Multiple antibody detection in 'seronegative' myasthenia gravis patients. (4th May 2017) - Hong, Y.; Zisimopoulou, P.; Trakas, N.; Karagiorgou, K.; Stergiou, C.; Skeie, G. O.; Hao, H.‐J.; Gao, X.; Owe, J. F.; Zhang, X.; Yue, Y.‐X.; Romi, F.; et al.
Abstract : Background and purpose: Myasthenia gravis (MG) is an autoimmune disease caused by antibody mediated impairment in the neuromuscular junction. Seronegative MG (SNMG) without antibodies against acetylcholine receptor (AChR) and muscle‐specific kinase (MuSK) by routine assays accounts for about 20% of all MG patients. Methods: Plasma from 81 Chinese MG patients previously found to be seronegative was tested by routine assays for AChR and MuSK antibodies. These samples were screened by (i) a novel, highly sensitive radioimmunoassay for AChR antibodies; (ii) cell‐based assays for clustered AChR, MuSK and lipoprotein receptor‐related protein 4 (LRP4) antibodies; (iii) a radioimmunoassay for titin antibodies. Results: Antibodies to AChR, MuSK, LRP4 and titin were found in 25% (20/81), 4% (3/81), 7% (6/81) and 6% (5/78) of SNMG patients, respectively. In total, 37% of SNMG patients were found to be positive for at least one of the tested antibodies. AChR antibody positive patients had more severe disease ( P = 0.008) and a trend towards fewer remissions/minimal manifestations than AChR antibody negative patients. The four patients with coexistence of antibodies had more severe disease, whilst the seronegative patients had milder MG ( P = 0.015). Conclusions: Detection of multiple muscle antibodies by more sensitive assays provides additional information in diagnosing and subgrouping of MG and may guide MG treatment.